PENYULUHAN DOOR TO DOOR TENTANG COVID-19 DAN ISOLASI MANDIRI DI DESA SUKAMELANG KECAMATAN KROYA KABUPATEN INDRAMAYU - Setyo Dwi Widyastuti; Aldi Pristy Ghamely Setiawan; Siti Khusnul Khotimah; Maila Mitamumtazah (Diseminasi: Jurnal Pengabdian kepada Masyarakat, 2022)
Covid-19 cases have increased in almost all areas in West Java, one of which is in Indramayu Regency. A total of 9,795 were confirmed positive for Covid-19, 1,179 people are still being treated, 8,353 have recovered and 263 people have died. Kroya District as one of the sub-districts in Indramayu Regency as of July 10, 2021, there were 116 confirmed cases of Covid-19 and in Sukamelang Village as of July 12, 2021, based on secondary data obtained from the Kroya Health Center, the prevalence of Covid-19 cases was 29 people. Confirmed positive, 14 people are doing isoman, 15 people have completed isolation / recovered. The purpose of this service activity is to increase public knowledge about Covid-19 and self-isolation in accordance with government recommendations. Counseling activities are carried out door to door with the target of all RT heads in Sukamelang Village. Counseling is done by the lecture method. The media used were leaflets, mobile phones, pre-test and post-test sheets. The counseling activity succeeded in increasing the knowledge of the RT Chair about Covid-19 and self-isolation. This can be seen from the increase in the value of knowledge from before and after the counseling was carried out, which was 11.2. Kasus Covid-19 meningkat hampir di semua wilayah yang ada di Jawa Barat, salah satunya adalah di Kabupaten Indramayu. Sebanyak 9.795 terkonfirmasi positif Covid-19, 1.179 orang masih perawatan, 8.353 sembuh dan 263 orang meninggal dunia. Kecamatan Kroya sebagai salah satu kecamatan di Kabupaten Indramayu per tanggal 10 Juli 2021 kasus Covid-19 terdata 116 orang yang terkonfirmasi positif dan di Desa Sukamelang per tanggal 12 Juli 2021 berdasarkan data sekunder yang diperoleh dari Puskesmas Kroya prevalensi kasus Covid-19 sebanyak 29 orang yang terkonfirmasi positif, 14 orang sedang melakukan isoman, 15 orang selesai isolasi/sembuh. Tujuan dari kegiatan pengabdian ini meningkatkan pengetahuan masyarakat tentang Covid-19 dan isolasi mandiri sesuai dengan anjuran pemerintah. Kegiatan penyuluhan dilakukan secara door to door dengan sasaran seluruh Ketua RT di Desa Sukamelang. Penyuluhan dilakukan dengan metode ceramah. Media yang digunakan adalah leaflet, handphone, lembar pre-test dan post-test. Kegiatan penyuluhan berhasil meningkatkan pengetahuan Ketua RT tentang Covid-19 dan isolasi mandiri. Hal ini dapat dilihat dari peningkatan nilai pengetahuan dari sebelum dan sesudah penyuluhan dilakukan, yaitu sebesar 11,2.